Case report: Surgical treatment of McCune-Albright syndrome with hyperthyroidism and retrosternal goiter: A case report and literature review - Xing, Zhiwei; Tao, Gongshuai; Pan, Wanwan; Wu, Delin; Pan, Tingting; Wan, Lingfeng; Ma, Xiaopeng; Wang, Yangyi (Frontiers in Surgery, 2023)
Introduction: McCune-Albright syndrome (MAS) is a low-incidence syndrome consisting of the clinical triad of fibrous structural dysplasia of bone, endocrine disease, and skin pigmentation. Thyroid dysfunction is the second most common endocrine dysregulation in MAS. However, there are no treatment guidelines for MAS complicated with hyperthyroidism. Notably, no case of MAS complicated with retrosternal goiter and hyperthyroidism has been reported to our knowledge. Case presentation: We report a 27-year-old man with MAS who developed the typical triad of bone fibrous dysplasia, skin pigmentation and hyperthyroidism, complaining of recent fast-growing neck mass and difficulty in breathing. Hyperthyrodism was under control by Thiamazole, and computed tomography showed an enlarged thyroid extending retrosternally. We performed a total thyroidectomy on the patient. At the 1-year follow-up, the patient’s dyspnea, hyperthyroidism, and bone pain were all significantly alleviated. Review: We searched the literature for previous case reports concerning MAS patients complicated with thyroid dysregulation. A total of 17 articles and 22 patients were identified to form our database. Among them, 9 studies clearly mentioned surgical intervention in 11 patients, and prognoses were also reported. Surgery was the most common intervention chosen and indicated a satisfactory prognosis. Conclusion: We report a rare case of MAS patient complicated with retrosternal goiter and hyperthyroidism. Our review provides an overview of MAS cases requiring interventions on thyroid function, and total thyroidectomy should be a proper treatment for these patients.